Antioxidant, cytotoxic and catalytic degradation efficiency of controllable phyto-synthesised silver nanoparticles with high stability using Cordia myxa extract. Issue 1 (1st January 2019) - Samari, Fayezeh; Parkhari, Parinaz; Eftekhar, Ebrahim; Mohseni, Fatemeh; Yousefinejad, Saeed
Abstract: This study aimed to report a one-pot, eco-friendly and room temperature procedure to prepare highly stable (at least 15 months) silver nanoparticles (AgNPs) using the aqueous leaf extract of Cordia myxa . The effects of different parameters, such as applied pH in the reaction mixture, amount of the leaf extract, silver ion concentrations, time of reaction and synthesis temperature, on the formation of NPs and their Surface Plasmon Resonance (SPR) spectra were studied. The characterisation of the prepared AgNPs was done using UV-Vis spectroscopy, Fourier Transform Infrared (FTIR), X-Ray Differentiation (XRD) and Transmission Electron Microscope (TEM) techniques. The shape of the synthesised AgNPs was spherical and it sized 3–10 nm with a face-centred cubic structure with SPR spectra at 410 nm. A possible reaction mechanism of AgNP formation by biomolecules of C. myxa was also introduced. The efficiency of the synthesised AgNPs as an excellent catalyst for the reduction of organic azo dyes using NaBH4 was proved. Dose-dependent cytotoxic activity of the prepared AgNPs against SW480 and HCT116 human colon cancer cell lines was also shown using MTT assay. Furthermore, the Ferric-Reducing Antioxidant Power (FRAP) assay was utilised to confirm the antioxidant activity of NPs. Non-toxic reagents and low-cost synthesis were the main features that made these AgNPs more attractive for chemical/biomedical applications. Abstract :